Influence of Oxidative Stress on Catalytic and Non-glycolytic Functions of Glyceraldehyde-3-phosphate Dehydrogenase - Muronetz, Vladimir I.; Melnikova, Aleksandra K.; Saso, Luciano; Schmalhausen, Elena V. (Current Medicinal Chemistry, 2020)
Background: Glyceraldehyde-3-phosphate Dehydrogenase (GAPDH) is a unique enzyme that, besides its main function in glycolysis (catalysis of glyceraldehyde-3-phosphate oxidation), possesses a number of non-glycolytic activities. The present review summarizes information on the role of oxidative stress in the regulation of the enzymatic activity as well as non-glycolytic functions of GAPDH. Methods: Based on the analysis of literature data and the results obtained in our research group, mechanisms of the regulation of GAPDH functions through the oxidation of the sulfhydryl groups in the active site of the enzyme have been suggested. Results: Mechanism of GAPDH oxidation includes consecutive oxidation of the catalytic Cysteine (Cys150) into sulfenic, sulfinic, and sulfonic acid derivatives, resulting in the complete inactivation of the enzyme. The cysteine sulfenic acid reacts with reduced glutathione (GSH) to form a mixed disulfide (S-glutathionylated GAPDH) that further reacts with Cys154 yielding the disulfide bond in the active site of the enzyme. In contrast to the sulfinic and sulfonic acids, the mixed disulfide and the intramolecular disulfide bond are reversible oxidation products that can be reduced in the presence of GSH or thioredoxin. Conclusion: Oxidation of sulfhydryl groups in the active site of GAPDH is unavoidable due to the enhanced reactivity of Cys150. The irreversible oxidation of Cys150 is prevented by Sglutathionylation and disulfide bonding with Cys154. The oxidation/reduction of the sulfhydryl groups in the active site of GAPDH can be used for regulation of glycolysis and numerous side activities of this enzyme including the induction of apoptosis.
Keywords: oxidative stress